Efficacy and safety of adjunctive corticosteroids therapy for patients with severe community-acquired pneumonia: A systematic review and meta-analysis - Huang, Jing; Guo, Jiquan; Li, Hongtao; Huang, Weibin; Zhang, Tiantuo (Medicine (Baltimore), 2019)
The systemic use of corticosteroids for patients in severe community-acquired pneumonia (CAP) remains disputed in clinical practice. We undertook a systematic review and meta-analysis to assess the efficacy and safety of corticosteroids in patients with severe CAP. We searched MEDLINE (1946 to June 2018), EMBASE (1966 to June 2018), and the Cochrane Library database for randomized controlled trials (RCTs) conducted for severe CAP. The endpoints of the study included total mortality, length of intensive care unit (ICU) stay and mechanical ventilation. Nine trials which contained 914 patients were included for final meta-analysis. Of the 488 patients in the corticosteroid group, there were 37 deaths (7.58%) and 56 deaths occurred in 426 patients in the control group (13.1%). Corticosteroid therapy was associated with a lower rate of all-cause mortality compared to control (odd ratio [OR] 0.63, 95% confidence interval [CI] 0.42-0.95, P = .03). Subgroup analysis was conducted to show that the drug type modified the effect of steroids for mortality rate: prednisolone or methylprednisolone therapy (OR 0.37, 95% CI 0.19-0.72) reduced total mortality, whereas hydrocortisone use did not (OR 0.90, 95% CI 0.54-1.49). We found the length of ICU stay was significantly shorter in the steroid group compared to control (MD -2.52 days, 95% CI -4.88 to -0.15; P = .04). And there was a reduction trend in the need for mechanical ventilation in corticosteroid group (OR 0.53, 95% CI 0.28-1.02; P = .06). There was no trend towards more adverse events in the corticosteroid arm compared to control (OR 0.92, 95% CI 0.58-1.47; P = .74). Overall, adjunctive systemic corticosteroids therapy was effective and safe for patients with severe CAP. In addition, the effects of mortality may differ according to the type of corticosteroids.